PENGEMBANGAN E-MODUL (MODUL DIGITAL) DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Kuncahyono - (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
Based on needs analysis, teachers have not fully utilized technology-based media and teaching materials. The teacher also has not fully produced technology-based media and teaching materials. The purpose of this research is to produce practical e-module teaching materials in thematic learning. This research method uses ADDIE research and development model. The results of the study that e-modules were developed through stages of needs analysis, prototype design, prototype development, field testing, and product evaluation. The results of field trials related to practicality resulted in a score of 86,5% with practical criteria. The response of students and teachers shows that the use of e-modules is easy to use because it is user-friendly with the support of integrated e-module content with internet links web based learning.